1998
DOI: 10.1089/neu.1998.15.837
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Crossover Trial of Fampridine-SR (Sustained Release 4-Aminopyridine) in Patients With Incomplete Spinal Cord Injury

Abstract: A randomized double-blind dose-titration crossover trial of the safety and efficacy of oral fampridine-SR (sustained release 4-aminopyridine) was conducted on spinal cord injured (SCI) patients at two centers. Twenty-six patients (n = 26) with incomplete lesions completed the trial. These patients all had chronic (>2 years) and stable neurological deficits. They received fampridine-SR 12.5 and 17.5 mg b.i.d. over a 2-week treatment period, followed by a 1-week washout and 2 weeks of placebo, or vice versa. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 59 publications
3
82
2
Order By: Relevance
“…The lack of quantitative gait improvement contradicts studies that reported gait improvement of subjects. 8,12 This discrepancy between perceived changes in function and a lack of quantitative changes was also seen in the present trial and may be due to several issues. Positive comments from subjects may be attributed to a Hawthorne effect, high expectations 12 or differences in the definition of improvement.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The lack of quantitative gait improvement contradicts studies that reported gait improvement of subjects. 8,12 This discrepancy between perceived changes in function and a lack of quantitative changes was also seen in the present trial and may be due to several issues. Positive comments from subjects may be attributed to a Hawthorne effect, high expectations 12 or differences in the definition of improvement.…”
Section: Discussionsupporting
confidence: 52%
“…8,12 This discrepancy between perceived changes in function and a lack of quantitative changes was also seen in the present trial and may be due to several issues. Positive comments from subjects may be attributed to a Hawthorne effect, high expectations 12 or differences in the definition of improvement. Clinicians equate improvement with quantitative measures while subjects may perceive general positive changes due to an increase in energy level and mood.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[329][330][331] In people with incomplete SCI a sustained-release (oral) formula of 4-AP (Fampridine) was reported to improve sensory and motor function and reduce spasticity during treatment. 332 As a result of these encouraging data, Acorda Therapeutics (New York, USA) initiated two large, multicenter clinical trials testing 4-AP in chronic SCI (8) and published results of these trials may soon become available. 204 Animal experimentation with 4-AP is ongoing, in an effort to clarify the optimal parameters of 4-AP treatment.…”
Section: Stage Right: Progenitor Cellsmentioning
confidence: 99%
“…6,7 Most recently, a double-blind placebo-controlled study of a sustainedrelease 4-AP formulation in chronic incomplete SCI patients has demonstrated signi®cant e cacy on a number of neurological measures. 8 Changes in conduction in motor pathways have also been documented electrophysiologically in man using transcranial magnetic stimulation. 9 Together with a longer series of equivalent trials in multiple sclerosis, 10 ± 12 these studies indicate that 4-AP may be useful in the treatment of conduction de®cits in demyelinating conditions.…”
Section: Introductionmentioning
confidence: 99%